HUBUNGAN TINGKAT PENGETAHUAN TENTANG HIV/AIDS DENGAN SIKAP REMAJA PADA PERILAKU SEKSUAL PRANIKAH DI SMK WIDYA BATAM - Nur Azizah Ali; Yuditia Prameswari (Universitas Batam, 2017)
AIDS (Acquired Immuno Deficiency Syindrome) was first discovered in 1981. Every day there is new infection as many as 8500 people. WHO (World Health Organization) recorded about 20 million people died from AIDS. The purpose of this research is to know the Relationship Level of Knowledge About HIV / AIDS with Adolescent Attitudes toward Pranikah Sexual Behavior In SMK Widya Batam. The research design used cross sectional study method. Population and sample were 68 students Sampling using total sampling technique. Data was collected by questionnaire and univariate and bivariate data analysis using computer program. The result of research got good adolescent knowledge as much 46 responden (67,6%) and attitude of adolescent positive attitude as much 39 respondent (57,4%). There is correlation between knowledge level of HIV / AIDS with premarital sexual attitude, Chi-Square result obtained (p-value = 0,001) then probality <0,05. Conclusion from research result there is correlation between knowledge level about HIV / AIDSuk with adolescent attitude on premarital sexual behavior at SMK Widya Batam Year 2017. Suggestion for next researcher to be able to do observation to relationship of knowledge level with premarital sexual behavior